Analysis of the Influence of Perceived Usefulness and Perceived Ease of Use on Use Intention of Digital Payment Ovo - Putra, Irsan Herlandi; Enny Diah Astuti; Tanti Widia Nurdiani; Dina Fahma Sari; Ernawati (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to determine the influence of perceived usefulness and convenience on preferences for using Ovo e-money. This research is a quantitative study with an associative approach. Data was collected through questionnaires. The population studied was Ovo application users, with a sample of 100 respondents selected randomly using a random sampling technique. Data analysis uses multiple linear regressions. The research findings reveal that user perceptions of Ovo's ease of use and perceived benefits significantly impact their e-money preferences. These findings indicate that the more users find Ovo easy to use and the more they experience the benefits they obtain, the more likely they are to choose Ovo as their electronic payment method. The implication is that service providers like Ovo need to continue to improve the user experience by focusing on developing intuitive interfaces, offering attractive benefits such as discounts and cashback, and providing responsive customer service. In the face of intense competition in the digital payments industry, this strategy will help Ovo maintain and increase its market share. By understanding that perceived convenience and usefulness are key factors in user decisions, management can direct their efforts to continue providing significant added value to their users; thereby, management can strengthen its position in the increasingly competitive and growing market in the digital payments industry.